1988
DOI: 10.1016/1010-7940(88)90008-5
|View full text |Cite
|
Sign up to set email alerts
|

Surgical therapy in lung cancer with single brain metastasis

Abstract: From January 1975 to April 1987, 27 patients underwent surgical resection of non oat cell lung cancer and a single brain metastasis. There were 25 men and 2 women ranging in age from 37 to 70 years. In 21 cases the brain metastasis was synchronous while in 6 cases the onset was metachronous. In 17 cases, the site of the brain metastasis was supratentorial and in 10 cases it was located in the posterior fossa. The chest X-ray confirmed the primary lung tumour in 24 cases. In 3 cases, only bronchoscopy and cytol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Others have reported similar findings. 5,32,69,70 In general, the median interval between the diagnosis of lung cancer and the discovery of brain metastases is 6 months, but 10% of our patients with adenocarcinoma did not receive a diagnosis of brain metastasis until more than 2 years after diagnosis of their primary tumor. For five patients, the interval was even longer-more than 5 years-a time period that was also reported by Komaki and colleagues.…”
Section: Histopathological Findingsmentioning
confidence: 84%
“…Others have reported similar findings. 5,32,69,70 In general, the median interval between the diagnosis of lung cancer and the discovery of brain metastases is 6 months, but 10% of our patients with adenocarcinoma did not receive a diagnosis of brain metastasis until more than 2 years after diagnosis of their primary tumor. For five patients, the interval was even longer-more than 5 years-a time period that was also reported by Komaki and colleagues.…”
Section: Histopathological Findingsmentioning
confidence: 84%
“…The prognosis of NSCLC is poor because metastasis develops early, and most patients present as advanced stage with metastasis to other organs. To date, multiple studies have showed a significant survival benefit from resection of a solitary metastatic lesion in the brain or the adrenal gland, and this practice is becoming the standard of care, especially if the primary lung tumor is in the early stages and resectable [3][4][5][6][7][8][9][10][11]. In some studies, the 5-year survival rate reaches the historical survival of patients with the same intra-thoracic stage NSCLC without metastasis [3][4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…In several series, 5-year survival rates of 15-35% had been reported after resection of solitary brain metastasis [3][4][5][6][7]. Likewise, other studies had shown that resection of isolated adrenal gland metastasis can result in long term survival (up to 26% at 5 years, and a median survival of 11-31 months) [8][9][10][11].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…It has long been recognized that patients with a solitary brain metastasis and limited thoracic disease might experience favorable long-term survival after effective local therapy [ 4 ]. Historically, cohort studies published during the 1980s with treatment dating back to even earlier decades already described the concept of surgical treatment in NSCLC with a solitary brain metastasis, which resulted in variable rates of 5-year survival [ 5 ]. Later on, stereotactic radiosurgery was used for some patients with brain metastases, and more recently, the introduction of extracranial stereotactic ablative radiotherapy has enabled us to provide noninvasive highly efficacious local therapy to different sites of oligometastases [ 6 ].…”
Section: Introductionmentioning
confidence: 99%